Implementation of PAI Learning Outcomes in Student Discipline in State Elementary School 15 Sungai Geringging Padang Pariaman Regency - Nurtib J. (Ruhama : Islamic Education Journal, 2021)
PAI learning is expected to produce changes in the behavior, attitudes and morals of learners, because actually the main orientation of PAI learning is the realization of learners who are able to practice Islamic teachings in accordance with the material that has been studied. Based on the above thoughts, this study aims to reveal how PAI learning outcomes are implemented for the discipline of learners in the school environment. This research uses qualitative methods, namely revealing data and facts in the form of sentences that can be understood by readers. The result of this study is that PAI learning results have not been implemented in the discipline of learners, the conclusion is based on research data that shows there are still learners who have not instilled discipline in the school environment.